American in disguise - Okimoto, Daniel I. (Walker/Weatherhill, 1971)
This will be for many years a valued document of the genesis of Japanese-American attitudes... The most constructive aspect of the book is that although the author went to Japan, he also returned to the United States, and the value of his work not merely about a oung Japanese-American.